Experimental and Numerical Research on Defective Shield Segment under Cyclic Loading - Long-gang Tian; Zhi-qiang Hu; Jie Chen (Shock and Vibration)
The retaining structure of a shield tunnel is usually subjected to static loading; however, cyclic loading such as the vibration loading of the train will act on the lining structure year after year that cannot be neglected. Due to the complex manufacturing and assembling process of the lining segment, initial defects in the segment are inevitable. Such defects will propagate under the cyclic loading such as the train vibration, which may cause a large threat to the shield tunnel system. In this paper, a defective shield tunnel lining segment under cyclic loading is studied by both a full-scale experiment and three-dimensional numerical simulations to investigate its fracture properties and failure mechanism and make a rational estimate of its fatigue life. Results show that crack propagation of the defective shield tunnel segment can be identified as several different stages based on its deformation characteristics, and the failure pattern of the segment is determined by its initial defects. The results by the experiment and numerical investigation are in good agreement for each other.